PENGARUH MODEL KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR PADA MATERI EKOSISTEM DI SMP - Kardiani, Vina; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find out the effect of picture and picture cooperative model on the learning outcomes in material of ecosystems in class VII of SMPN 2 Kembayan. This research used quasi experimental design with nonequivalent control group design. Research samples were class VII C as the experimental class and VII B as the control class, with a sampling technique of intact group. The instrument used  the multiple choice test with a total of 20 questions. The average learning outcomes in the experimental class was 13.79, while the control group was 12.34. The results of the t test analysis showed that tcount > ttable namely 2.20 > 1.67, this means that there are significant differences between the learning outcomes of students taught using Picture and Picture cooperative  model and the learning outcomes of students taught using a conventional learning model. The effect size obtained 0.62 in the moderate category and gave the contribution 23.24%  of student learning outcomesKeywords: Picture and Picture cooperative model, learning outcomes, material of ecosystem